In Gold We Trust : Social Capital and Economic Change in the Italian Jewelry Towns (Book collections on Project MUSE., 2007)
"In Gold We Trust is a historical and sociological account of how, by the late 1960s, three small Italian towns had come to lead the world in the production of gold jewelry - even though they had virtually no jewelry industry less than a century before, and even though Italy had western Europe's most restrictive gold laws. It is a story of how northern Italy performed its post-World War II economic miracle by creating localized but globally connected informal economies, in which smuggling, tax evasion, and the violation of labor standards coexisted with ongoing deliberation over institutional change and the benefits of political participation."--Jacket.